Modeling the effect of temperature on the hydration kinetic whole moong grain - Vijay Singh Sharanagat; Vidushi Kansal; Kshitiz Kumar (Journal of the Saudi Society of Agricultural Sciences)
Water hydration characteristics of moong at temperatures of 25, 35, 45 and 55 °C were determined and three major dimensions (length, width and thickness) and moisture content were determined at time interval varying from 0 to 500 min. Peleg’s model and Fick’s second law of diffusion were used to simulate water absorption and effective diffusivity with varying temperature. Peleg’s equation was adequately capable of predicting the experimental condition and the rate constants k1 and k2 were decreased with increased soaking water temperature from 0.5132 to 0.1081 and 0.0165 to 0.151, respectively. Effective diffusivity of water increases from 1.12 × 10−11 to 1.98 × 10−11 m2/s over the temperature range. Reduction of activation energy with temperature and temperature dependency of diffusivity coefficient was also described by Arrhenius equation. Keywords: Water absorption, Peleg’s model, Fick’s law, Activation energy, Diffusion